Analysis of the repeated sprints ability with and without change of direction in professional soccer players - Yanci Irigoyen, J.; Azcarate, U.; Los Arcos, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The aims of this study were to analyze the performance in repeated straight line sprint (RSA) and repeated sprints with change of direction (RCODA) in soccer players. The study involved 18 professional soccer players. Results showed that considerably greater time was needed to perform subsequent 15 and 30 m RCODA (p < 0.01, d =1.29-4.11) in comparison to same distancesRSA.However, differences in relation to fatigue indexes at both 15m (IF15 m) and 30 m (IF30 m) were not statistically different when performing RSA and RCODA (p > 0.05, d = 0.18-0.43). Despite the fact that the association between RSA and RCODA was either high or very high and very likely at the majority of the sprints, at the best track record and total time, the obtained association for IF15 m and IF30 m was small or moderate and not significant.